ELT Graduate Students’ Challenges of Writing for Scholarly Publication: Discursive Perspectives - Masyhudi Lathif; Joko Nurkamto; Diah Kristina (Hasanuddin University, 2021)
There has been an increasing demand for postgraduate students to publish their scholarly work as one of their graduation requirements. The present study attempted to explore the graduate students’ challenges in writing for scholarly publication seen from the perspectives of discursive challenges. This qualitative research employed case study to disclose the participants’ perceived constraints. The students participated in this study three final-year female students undertaking their master’s degree in English Language Teaching (ELT) in a university in Central Java. Data were garnered from semi-structured interviews. The findings discovered the discursive challenges that the participants faced in writing for scholarly publication including accuracy, genre understanding, interference of L1 to L2 production, and lexical items. It is expected that this study provides new insights for EAP design for higher education context so that the program addresses the needs of the graduate students.